2017
DOI: 10.1371/journal.pntd.0005387
|View full text |Cite
|
Sign up to set email alerts
|

Partnering for impact: Integrated transmission assessment surveys for lymphatic filariasis, soil transmitted helminths and malaria in Haiti

Abstract: BackgroundSince 2001, Haiti’s National Program for the Elimination of Lymphatic Filariasis (NPELF) has worked to reduce the transmission of lymphatic filariasis (LF) through annual mass drug administration (MDA) with diethylcarbamazine and albendazole. The NPELF reached full national coverage with MDA for LF in 2012, and by 2014, a total of 14 evaluation units (48 communes) had met WHO eligibility criteria to conduct LF transmission assessment surveys (TAS) to determine whether prevalence had been reduced to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 11 publications
(12 reference statements)
0
18
0
Order By: Relevance
“…Since 2014, the PNCM has been able to take advantage of the ongoing LF TAS in 21 of 23 total evaluation areas in the country to obtain information on malaria transmission by conducting an integrated TAS. 41 Preliminary results from one evaluation area, the Department of Nippes, that incorporated malaria testing into the LF TAS, found zero children who were positive by RDT. However, serology results from the same children showed that those in 34 of the 43 schools had evidence for previous exposure to malaria by the presence of antibodies against P. falciparum (PNCM data/Rogier E, personal communication).…”
Section: Strengthening and Expanding Surveillance To Identify Malariamentioning
confidence: 99%
“…Since 2014, the PNCM has been able to take advantage of the ongoing LF TAS in 21 of 23 total evaluation areas in the country to obtain information on malaria transmission by conducting an integrated TAS. 41 Preliminary results from one evaluation area, the Department of Nippes, that incorporated malaria testing into the LF TAS, found zero children who were positive by RDT. However, serology results from the same children showed that those in 34 of the 43 schools had evidence for previous exposure to malaria by the presence of antibodies against P. falciparum (PNCM data/Rogier E, personal communication).…”
Section: Strengthening and Expanding Surveillance To Identify Malariamentioning
confidence: 99%
“…Human subjects. Samples were collected in Haiti in May 2015 from the Saut d'Eau commune and in April 2016 from the Grand Anse department as part of a lymphatic filariasis (LF) transmission assessment survey 27 , with integration of malaria RDTs and soil-transmitted helminth microscopy of stool specimens 43 . Before enrollment, informed consent forms were sent home with each of the students so parent or legal guardian could read and sign for return to the study teams.…”
Section: Methodsmentioning
confidence: 99%
“…Using the tables provided by WHO 44 , the target sample size and the critical cut-off threshold was determined and if the number of positive children identified fell below the critical cut-off threshold, the recommendation was made to stop mass-drug administration (MDA) for LF. Upon completion of MDA, TAS surveys were conducted to determine whether populations have reached the critical threshold of infection prevalence (<2% antigenemia), below which LF transmission is likely no longer sustainable 43 .…”
Section: Methodsmentioning
confidence: 99%
“…countries [24][25][26]. This experience led to the recommendation in the WHO guidelines to assess the epidemiology of STH during LF-TAS [2]: the target population for the STH survey in conjunction with LF-TAS is designated as 8-10-year-olds for school-based surveys and 6-7-year-olds for household surveys.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%